The Algebra of Need - Cruz, Julian (Re-visiones, 2024)
Through stories, writers and two music bands, I have taken that all the characters I'm dealing with have maintained a close relationship that united them all with a smart form of radicalism. At the dawn of an increasingly totalitarian society, it should be reminded that certain uncomfortable and strage events, far from violence, can halt the world and provoke it panic.